Jornalismo de proximidade e hiperlocal: smartphones na produção da notícia no telejornalismo - Pinto, Adriana Bagno Alves (2020)
The research proposes as object of study to investigate the production routine in the journalism of the Tambaú Communication Network in a context of convergence from the concepts of proximity and hyperlocal journalism. The work aimed to research the implications arising from digital technologies in the newsroom and observe the impact of the use of smartphones in the production process of telejournalism in Paraíba. The study has as its empirical object the Rede Tambaú de Comunicação and the content produced and distributed by smartphones, in addition to its impact on its audience. The work delimited as corpus the journalistic program of RTC, Tambaú da Gente. The program was analyzed in person in September 2019. The methodology used was field research with participant observation and field diary, with semi-structured interviews, and analysis and interpretation in the light of content analysis. The main concepts worked on were proximity journalism, convergence, a culture of participation and the concept of digital mobile journalism. The results obtained were in the sense of understanding the new configuration of the journalist in the media ecosystem with the introduction of tools available today on smartphones for the production and distribution of journalistic and entertainment content.